Dynamic Assessment of Fibrinogen Adsorption and Secondary Structure Perturbation. (6th April 2014) - Khot, Gaurang; Kuforiji, Folashade; Wright, Rupert; Roach, Paul
Abstract : Fibrinogen is a protein being of prime importance for the initiation of clotting and thrombus formation, readily adsorbed onto surfaces presenting both hydrophilic and hydrophobic nature. The mechanism of adsorption, and thus the final presentation of this protein are therefore important for subsequent involvement for, for example, platelet adhesion. Biological activity can be controlled through careful consideration of material design; here we report kinetic assessment of fibrinogen adsorption onto plasma polymerised allylamine (hydrophilic) and hexane (hydrophobic) surfaces, using FTIR-ATR to inform on kinetics of adsorption, secondary structure evaluation, and orientational variation. Fibrinogen was found to respond differently to these two surfaces, adsorbing more rapidly to hydrophilic surfaces and losing an ordered secondary structure over a much longer timescale compared to hydrophobic surfaces.